ANALISIS DAMPAK ALOKASI DANA KESEHATAN TERHADAP TINGKAT KESEJAHTERAAN MASYARAKAT KOTA SABANG - Dedi Hardian; Diana Sapha (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract This study aims to determine the effect of health budget allocation on the level of community welfare in Sabang City and health service providers allocate health budgets in Sabang City Hospital with the aim of improving the quality of health services that affect the costs incurred by the community. This research method uses quantitative and qualitative descriptive analysis research methods and uses primary data through observation and questionnaires. This research was conducted in the city of Sabang by taking a sample of 100 household head respondents who used health services in Sabang City Hospital, each of which 25 prosperous family heads in Sukakarya and Sukajaya sub-districts and 25 Pre-prosperous family heads in Sukakarya and Sukajaya sub-districts. The results showed that the community using health services is the head of the family who bears a large burden by the family head, namely the cost of food and food as well as referral medical expenses and accompanying family members who are borne by the head of the family up to more than Rp.4,000,000 per month only a little Rp1,000,000 to Rp.3,300,000. If the government as a provider of health services optimizes the budget allocation for good health in providing health services in the Sabang City Hospital, the middle to lower class community is not charged with the costs of buying medicines, medical expenses for other hospitals and other unexpected costs.Keyword: Health Fund Allocation, Public Welfare, Sabang city, Impact of Allocation, Public Health.